Research Progress on the Application of Probiotics and Fermentation Products in Gastrointestinal Cancers - Cai Mengqi (BIO Web of Conferences, 2025)
Cancer is the second leading cause of death globally, and gastrointestinal cancer is one of the most common types of cancer. Recent population-based studies show that the incidence rates of gastrointestinal cancers such as gastric cancer and colorectal cancer are on the rise worldwide. This article mainly reviews the application of probiotics and their their metabolic byproducts in gastric cancer and colorectal cancer. Probiotics and their metabolic byproducts demonstrate significant therapeutic potential in gastric cancer and colorectal cancer. Currently, the main treatment method for gastric cancer and colorectal cancer is surgical treatment. However, due to a large number of recurrence cases, there is an urgent need to develop new therapies. Probiotics, as complementary and alternative therapies for gastric cancer and colorectal cancer, are becoming increasingly popular. One of the major pathogenesis mechanisms of gastric cancer is the infection of Helicobacter pylori. Probiotics can treat gastric cancer by inhibiting the infection of Helicobacter pylori and regulating the immune system. For colorectal cancer, probiotics can treat it by regulating the gut microbiome, enhancing gut barrier competence and regulating the immunological network. When using probiotics, attention should be paid to the control of dosage, the management of safety, and the monitoring of activity.